1985
DOI: 10.1007/bf00395046
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography-mass spectrometry evidence for several endogenous auxins in pea seedling organs

Abstract: Qualitative analysis by gas chromatography-mass spectrometry (GC-MS) of the auxins present in the root, cotyledons and epicotyl of 3-dold etiolated pea (Pisum sativum L., cv. Alaska) seedlings has shown that all three organs contain phenylacetic acid (PAA), 3-indoleacetic acid (IAA) and 4-chloro-3-indoleacetic acid (4Cl-IAA). In addition, 3-indolepropionic acid (IPA) was present in the root and 3-indolebutyric acid (IBA) was detected in both root and epicotyl. Phenylacetic acid, IAA and IPA were measured quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 33 publications
4
46
0
1
Order By: Relevance
“…These auxin metabolites were targeted for quantification because a previous study suggested their presence in M. truncatula based on enzyme feeding assays (Campanella et al, 2008). The detection limits for these auxins are shown in Supplemental Table 1 and are below the concentrations measured for some of these auxins in other studies (Schneider et al, 1985;Kowalczyk and Sandberg, 2001;Matsuda et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…These auxin metabolites were targeted for quantification because a previous study suggested their presence in M. truncatula based on enzyme feeding assays (Campanella et al, 2008). The detection limits for these auxins are shown in Supplemental Table 1 and are below the concentrations measured for some of these auxins in other studies (Schneider et al, 1985;Kowalczyk and Sandberg, 2001;Matsuda et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Entomopathogenic bacteria have been recently reported to produce plant growth regulators (Raddadi et al 2008), that not only improve plant growth and development but also enhance the fitness of the host against a diverse array of environmental stresses Kang et al 2012). Bacteria produce GAs in culture extract that can be detected using gas chromatography coupled with mass spectrometry (GC/ MS) with selected ion monitoring mode (SIM), which has been used extensively for the analysis of metabolites because of its greater separation efficiency that resolves very complex biological mixtures (Schneider et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…El tipo de auxina más abundante en la naturaleza es el ácido indol-3-acético (AIA), ya que el ácido indol-3-butírico (AIB) se encuentra en menores cantidades en las plantas (Schneider et al, 1985). Entre las hormonas sintéticas se encuentra el AIB, un regulador del crecimiento que promueve y acelera la formación de raíces adventicias en las plantas.…”
Section: Introductionunclassified
“…The most abundant type of auxin in nature is indole-3-acetic acid (IAA), since indole-3-butyric acid (AIB) is found in lesser amounts in plants (Schneider et al, 1985). AIB is among the synthetic hormones, a growth regulator that promotes and accelerates the formation of adventitious roots in plants.…”
Section: Introductionmentioning
confidence: 99%